2016
DOI: 10.5935/medicalexpress.2016.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity static stretching does not modulate heart rate variability in trained men

Abstract: OBJECTIVE: To investigate the acute effect of static stretching on heart rate variability in trained men. METHODS: Eight subjects were randomly submitted to two situations, as follows: a static stretch protocol and 20 minutes at rest. The stretch protocol consisted of two sets of 30 seconds of static stretch of the chest muscles with a 40 second of interval between them. After 48 hours, the procedures were reversed so that all the subjects should were submitted to the two situations. The values of heart rate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Contrary to the previously mentioned findings, Silva et al (38) reported no significant changes in HR or HRV indices 10 minutes after ASTE in young trained men. A possible explanation for the discrepancy is that the volume of work completed during this ST intervention was not sufficient to produce significant changes in autonomic function at 10 minutes after intervention.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Contrary to the previously mentioned findings, Silva et al (38) reported no significant changes in HR or HRV indices 10 minutes after ASTE in young trained men. A possible explanation for the discrepancy is that the volume of work completed during this ST intervention was not sufficient to produce significant changes in autonomic function at 10 minutes after intervention.…”
Section: Resultsmentioning
confidence: 65%
“…Thus, higher volume active ST protocols might elicit greater cardiovagal increases after intervention. Another potential reason for the contrasting findings by Silva et al (38) may be the study population, as young trained individuals may require a significant higher volume of ST to elicit significant autonomic changes when compared with other untrained populations used on previous ST studies (11,18). Nevertheless, this notion is somewhat speculatory because HRV responses to a higher volume ASTE in trained individuals have not been evaluated to date.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In young men with low flexibility, SDNN and RMSSD were significantly increased 30 minutes after exercise consisting of 3 active static stretching movements (3 sets x 30s) involving the trunk and hamstring region (Farinatti et al, 2011). In another study, it was reported that there was no significant difference in the HRV parameters of the 20-minute static stretching of the chest area, consisting of 2x30 seconds, performed with trained men compared to the control group (Silva et al, 2016). Different results have been revealed in the applied stretching methods.…”
Section: Discussionmentioning
confidence: 92%
“…In many studies, it is stated that both recovery methods have positive effects, but there is no study on which recovery method is more effective (Griefahn et al, 2017;Kalén et al, 2017;Lastova et al, 2018). In addition, there are studies examining the effect of static stretching exercise on HRV in the literature (Farinatti, Brandão, Soares, & Duarte, 2011;Silva et al, 2016), but as far as we know, there is no study on how DS exercise affects HRV during recovery. Therefore, determining the possible changes in blood pressure (BP) and HRV of different recovery exercises will enable us to understand better the exercise programs that hearing-impaired athletes will follow during the next training or post-competition recovery process.…”
Section: Introductionmentioning
confidence: 99%